LEGAL AND ENVIRONMENTAL FRAMEWORKS FOR SUSTAINABLE ENERGY SECURITY - Khaitov Panji Bukharovich (Modern American Journals, 2025)
This study examines the legal and environmental foundations for ensuring sustainable energy security, with particular emphasis on the improvement and analysis of relevant normative legal documents. The paper discusses the theoretical framework of environmental law, the environmental-legal mechanisms for guaranteeing energy security, and the key challenges in advancing the system. Special attention is given to issues related to the regulation of energy law sources, the national and international significance of energy law within the natural resources framework, and the historical origins of the right to use such resources for scientific research. Furthermore, the article outlines the specific forms and methods through which environmental-legal measures for energy security are implemented in the energy sector.
Keywords: Sustainable energy security, energy, energy efficiency, environmental safety, renewable energy sources, subsoil resources, economic development, electric power, energy law.